Evaluasi Mutasi Pegawai di Pemerintahan Kabupaten Banyuasin - Juanda Heri; Alamsyah Alamsyah; Mega Nugraha (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Juanda Heri. This study aims to describe employee mutations in the Banyuasin Regency Government. This research was conducted for three months using a descriptive qualitative approach. Data was collected through interviews, observation, and documentation. Data analysis techniques are carried out by presenting data, reducing data, and drawing conclusions. The results showed that the Evaluation of Employee Movements in the Government of Banyuasin Regency. From the context aspect, employee transfers carried out by BKD often violate existing rules or SOPs, namely without paying attention to the agreed provisions such as having 2-5 years, must be in accordance with competence and good career development, the transfer process is often intervened due to political factors. From the input side, there are many things that, indeed, employee transfers are not done out of necessity, but because there are personal and political factors, employee transfers are often done because they don't want to work in that place, can be far from home and the like, staffing appointments as well and this becomes a problem. one of the main problems in the mutation process. For the aspect of transferring and transferring employees, it is often not carried out with appropriate steps and processes, this is because the transfer of employees is not due to the needs of the institution, but because of the dislike and personal interest of the employee. While the product aspect is expected to be better than employee transfer, namely to improve employee performance and work productivity in a new place, but this is often ignored because the purpose of performance transfer does not always consider the aspect of improvement, but from the aspect of interest. The supporting factor and being the biggest force in the employee transfer process is the policy that regulates this, namely BKN Regulation Number 5 of 2019 concerning Procedures for Implementing Transfers, by following these rules, of course the transfer process will not experience problems. While the inhibiting factor in the problem of employee transfer is again caused by the interests of the institution and increasing work productivity, but is caused by political factors, and in the future if it continues to be influenced by political interests, every time a regime change there will be a change of employees this will make it easier.